Inducing hypertrophic effects of type I skeletal muscle fibers: A hypothetical role of time under load in resistance training aimed at muscular hypertrophy. (March 2018) - Grgic, Jozo; Homolak, Jan; Mikulic, Pavle; Botella, Javier; Schoenfeld, Brad J.
Abstract: An emerging body of evidence is starting to suggest that the hypertrophy of skeletal muscle fibers might be load specific. In other words, it may be that resistance training with high loads (i.e., ≥60% of 1 repetition maximum [RM]) emphasizes a greater growth of type II muscle fibers, while resistance training with low loads (i.e., <60% of 1RM) might primarily augment hypertrophy of type I muscle fibers. Type I and type II muscle fibers possess certain distinct characteristics, with type II muscle fibers having faster calcium kinetics, faster shortening velocities, and ability to generate more power than type I muscle fibers. Alternatively, compared to type II fibers, type I muscle fibers have a higher oxidative capacity and a higher fatigue threshold. Due to the lower fatigability of type I muscle fibers, it may be hypothesized that a greater time under load is necessary to stimulate an accentuated growth of these fibers. An increase in time under load can be achieved when training with lower loads (e.g., 30% of 1RM) and to momentary muscular failure. The present paper discusses the hypothesis that a greater hypertrophy of type I muscle fibers may be induced with low load resistance training.